Revisiting Sample Bias in the UK's Annual Survey of Hours and Earnings, with Implications for Estimates of Low Pay and the Bite of the National Living Wage - John Forth; Alex Bryson; Van Phan; Felix Ritchie; Carl Singleton; Lucy Stokes; Damian Whittard (Institute of Labor Economics (IZA), 2024)
The Annual Survey of Hours and Earnings (ASHE) is based on an annual one per cent sample of employee jobs and provides many of the UK's official earnings statistics. These statistics are generated using official weights designed to make the achieved sample in each year representative of the population of employee jobs in Britain by gender, age, occupation, and region. However, we find that jobs in small, young, private-sector organisations remain under-represented after weighting. Additionally, there is evidence of systematic year-to-year longitudinal attrition among employees who remain in scope, for which no official weighting adjustment exists. We develop new weights to address these issues, demonstrating their importance through policy-relevant examples. Our new estimates suggest that the bite of the National Living Wage is greater, and that progress toward the target for eradicating low pay has been faster, than previously understood.
Keywords: C81; C83; J31; 330; earnings; non-response bias; attrition; survey weighting; low pay; national living wage